2015
DOI: 10.1161/circresaha.115.305919
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction and Inflammation

Abstract: A therosclerosis as a persistent arterial disease is characterized by an imbalanced lipid metabolism and maladaptive immune response, resulting in subendothelial lipoprotein retention and endothelial activation with continuous migration of leukocytes and smooth muscle cells to the inflamed intima. 1,2 Over decades, this leads to the formation of stable atheromas that induce chronic tissue ischemia or of vulnerable plaques that cause acute occlusive atherothrombotic complications, such as myocardial infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Atherosclerosis is a chronic inflammatory arterial disease developing over decades, characterized by an impaired lipid metabolism and imbalanced immune response, which lead to the subendothelial lipoprotein retention and activation of endothelial cells with continuous migration of leukocytes and smooth muscle cells to the inflamed intima. Acute occlusive atherothrombotic complications, such as myocardial infarctions (MI) and strokes, result from the formation of vulnerable atherosclerotic plaque (Hristov and Weber, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is a chronic inflammatory arterial disease developing over decades, characterized by an impaired lipid metabolism and imbalanced immune response, which lead to the subendothelial lipoprotein retention and activation of endothelial cells with continuous migration of leukocytes and smooth muscle cells to the inflamed intima. Acute occlusive atherothrombotic complications, such as myocardial infarctions (MI) and strokes, result from the formation of vulnerable atherosclerotic plaque (Hristov and Weber, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, immunomodulatory treatments such as interferon β have been found to be associated with the risk of CVD in MS patients [69]. In genetic terms, the causality found may be due to alterations in Human Leukocyte Antigen (HLA), CD40, and PINK1/Parkin genes in patients with MS and PD, which modulate the body's immune-inflammatory response and mitochondrial autophagy, thereby influencing the occurrence of myocardial infarction [70][71][72][73]. It's essential to acknowledge potential biases in these observational studies, such as confounding variables and subjective viewpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced inflammation response may lead to increased secretion of inflammatory cytokines such as TNF- α and IL-6. It was suggested that high levels of TNF- α or IL-6 may promote cardiomyocyte apoptosis [ 50 , 51 ]. Finally, excessive oxidative stress resulted in aggravated cardiac injury.…”
Section: Discussionmentioning
confidence: 99%